MAKNA DAN PESAN BERTATO (ANALISIS DESKRIPTIF KUALITATIF DALAM PANDANGAN PENGGUNA TATO DI STUDIO PRABOE JAZZ TATTOO YOGYAKARTA): makna dan pesan tatto - Mochammad Assad Fadlyan; Kristina Andryani (Program Studi Komunikasi Fakultas Ilmu Sosial dan Ilmu Politik Universitas Mulawarman, 2020)
A tattoo is an art of body painting that used human body as a medium to expert himself or herself. Praboe Jazz Tattoo Studio is one of tattoo studios located in Yogyakarta concerned with art tattoos. This place has been around since 1998. This place can be considered as one of the promoters for art tattoos to be known and expanded in Yogyakarta. The researcher selects this place for conducting the data of the study. Four informants are obtained through in-‐‑depth observations and interviews. The result show that for most part of people, tattoos can represent the identity of their user. Also, symbols in tattoos for some extent can embody a certain message and meaning of each person who wear them. These message and meaning are generally formed from their interaction to surroundings that become a self concept. In this case, each person may have distinctive self concept.